The Influence of Social Communication and Da'wah in Improving Arabic Speaking Skills - Burhanuddin; Davinna Sherenia Pramesti (al-Afkar, Journal For Islamic Studies, 2026)
The ability to speak Arabic is crucial for individuals learning the language, particularly for religious, academic, and professional purposes; however, many learners struggle to achieve fluency due to a lack of understanding of the cultural and social context. This study employed a descriptive qualitative approach with literature review as the data collection technique to explore how social communication and da'wah contribute to improving Arabic speaking skills. The hypotheses proposed are that social communication has a positive influence on improving speaking skills, da'wah as a communication medium contributes significantly to the development of speaking skills, and the combination of the two has a greater impact than either method alone. The results show that social communication creates an interactive environment that supports speaking practice, while da'wah enhances students' understanding of language structures and vocabulary appropriate to the social context. The combination of these two elements has proven effective in improving Arabic speaking skills, so this study is expected to contribute to the development of more interactive and applicable Arabic language learning methods.